Carbohydrate and fatty acid perturbations in the amniotic fluid of the recipient twin of pregnancies complicated by twin-twin transfusion syndrome in relation to treatment and fetal cardiovascular risk. (August 2016) - Dunn, Warwick B.; Allwood, J. William; Van Mieghem, Tim; Morris, R. Katie; Mackie, Fiona L.; Fox, Caroline E.; Kilby, Mark D.
Abstract: Introduction: Twin-twin transfusion syndrome (TTTS) complicates 15% of monochorionic twin pregnancies, often being associated with recipient cardiac dysfunction. Untreated, it has a fetal mortality rate of at least 90%; although treatment by fetoscopic laser coagulation significantly improves prognosis. Measurement of recipient amniotic fluid metabolites, such as cardiac Troponin T and atrial natriuretic polypeptide, correlate with cardiac function in this fetus. The aim of this study is to describe the amniotic fluid metabolomic profile in TTTS, relate this to fetal recipient cardiac function and assess the metabolomic changes induced by fetoscopic laser coagulation. Methods: Prospective single centre cohort study. The metabolomics profile of the amniotic fluid from the recipient sac of TTTS pregnancies was assessed using ultra high performance liquid chromatography-mass spectrometry. Profiles were compared pre- and post-laser coagulation and related to fetal recipient cardiac function, as assessed using Doppler ultrasound within 4 h of treatment. Results: Eleven metabolites had significant associations with recipient fetal right and left ventricular myocardial performance index pre-laser. 200 metabolites in recipient amniotic fluid demonstrated a change in relative concentrations when comparing pre- and post-laser coagulation ( p < 0.005). The most prominent change is in the balance of carbohydrate and fatty acid metabolic profile contributing to fetal or placental energy metabolism. These changes were also associated with the echocardiographic measures of recipient cardiac function. Discussion: Changes in carbohydrate and fatty acid metabolic profiles are noted in recipients with cardiac dysfunction, and further changes are noted after treatment. Validation and investigation may identify targets for potential pharmacological treatment. Highlights: Metabolomic changes are seen after fetoscopic laser coagulation (FLC). Carbohydrate and fatty acid metabolism appears altered following FLC. These findings are in keeping with changes seen in adults with cardiomyopathy. Metabolomics may provide new biomarkers for twin twin transfusion syndrome.